2005
DOI: 10.1111/j.1745-4514.2005.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of an Alkaline Protease From the Viscera of Bolti Fish (Tilapia Nilotica)

Abstract: An alkaline protease was extracted from acetone powder of the viscera of bolti fish (Tilapia nilotica) with distilled water, precipitated from the extract by 40–60% (NH4)2SO4and then dialyzed. Enzyme homogeneity studies by polyacrylamide gel electrophoresis (PAGE) illustrated that the enzyme was homogenous. Sodium dodecyl sulfate–PAGE showed a molecular weight of 23.0 kDa. The optimal pH and optimal temperature were 8.0 and 45C, respectively, with casein as a substrate. A remarkable stability was observed unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 10 publications
7
14
0
Order By: Relevance
“…Our results are in agreement with the previous observations reported, in spite of the fact that tilapia is an omnivorous fish species, with predominantly herbivorous feeding habits. Trypsin-like enzymes have been identified in tilapia (Bezerra et al 2005;El-Beltagy et al 2005). However, the relative contribution of specific proteases to the overall alkaline proteolytic activity was not assessed in this study and should be considered in further research.…”
Section: Discussionmentioning
confidence: 59%
“…Our results are in agreement with the previous observations reported, in spite of the fact that tilapia is an omnivorous fish species, with predominantly herbivorous feeding habits. Trypsin-like enzymes have been identified in tilapia (Bezerra et al 2005;El-Beltagy et al 2005). However, the relative contribution of specific proteases to the overall alkaline proteolytic activity was not assessed in this study and should be considered in further research.…”
Section: Discussionmentioning
confidence: 59%
“…Alkaline proteases from the red scorpionfish (Scorpaena scrofa) viscera exhibited optimal activity at pH 10.0 and 55C (Younes et al 2014). The optimal pH and temperature of alkaline protease from the viscera of bolti fish (Tilapia nilotica) were 8.0 and 45C, respectively, with casein as a substrate (El-Beltagy et al 2005). The optimum pH and temperature of serine protease from the viscera of sardinelle (Sardinella aurita) were around pH 8.0 and 60C, respectively (Ben et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…(2004) found that the molecular weight of isolated trypsin from the pyloric caeca of Monterey sardine was 25 kDa. El‐Beltagy et al. (2005) reported that purified alkaline protease from the viscera of Bolti fish had a molecular weight of 23 kDa.…”
Section: Resultsmentioning
confidence: 99%